Outpatient Cervical Ripening: A Cost-Minimization and Threshold Analysis - Son, Shannon L.; Benson, Ashley E.; Hart Hayes, Emily; Subramaniam, Akila; Clark, Erin A. S.; Einerson, Brett D. (American Journal of Perinatology, 2020)
Objective To evaluate cost of outpatient (OP) versus inpatient (IP) ripening with transcervical balloons, and determine circumstances in which each strategy would be cost saving.Study Design We created a decision model comparing OP and IP balloon ripening in term (≥37 weeks) singleton pregnancies with unfavorable cervix. We performed a cost-minimization analysis and threshold analyses comparing two OP ripening strategies (broad and limited use) to IP ripening from a health system perspective. Base case estimates of probability, utilization, and cost were derived from the literature. The primary outcome was incremental cost of OP versus IP ripening from a hospital perspective. One- and two-way sensitivity analyses explored uncertainty in the model.Results Both OP ripening strategies were cost saving compared with IP ripening: incremental cost −$228.40/patient with broad use and −$73.48/patient with limited use. OP ripening was no longer cost saving if hours saved on labor and delivery (L&D) were <3.5, insertion visit cost >$714, or facility cost/hour on L&D <$61. Two-way sensitivity analyses showed that OP ripening was cost saving under the most plausible clinical circumstances.Conclusion In patients with unfavorable cervix, OP transcervical balloon ripening was cost saving under a wide range of circumstances, particularly if OP ripening can shorten time spent on L&D by 3.5 hours.
Keywords: cervical ripening; outpatient ripening; cost effectiveness; balloon ripening; induction of labor